A Comparative Analysis of CO2 Emissions in India and Brazil Using the Logarithmic Mean Divisia Index - Karnik, Neha (IOSR Journal of Humanities and Social Science, 2025)
Background:Carbon dioxide (CO2 ) emissions related to energy grew by 1.1 percent globally and reached a new height of 37.4 Gt in 2023. In contrast, the Paris Agreement calls for a significant reduction in CO2 emissions. However, the percentage increase in emissions was significantly lower than the growth rate of the world GDP, which was 3 percent in 2023. In 2023, India stood at the third rank in terms of CO2 emissions. The Indian economy grew at a 6.7 percent annual rate, while CO2 emissions rose by 7 percent per annum in 2023 Materials and Methods: The purpose of the study is to use decomposition analysis to quantify the factors drive emissions of carbon dioxide (CO2 ). The Logarithmic Mean Divisia Index (LMDI) is used to examine the factors that influence sector-wise CO2 emissions from 2011 to 2021. The drivers of sectoral emissions of CO2 are divided into the population, economic activity, energy intensity, and carbon intensity. Identifying the drivers responsible for CO2 emissions in India and Brazil would help policymakers in determining the areas that require attention. Results: The study finds that in the case of India, population and economic activity effects have been always positive contributors to the sectoral CO2 emissions in India. However, economic growth has the dominant share in the sectoral CO2 emissions. Hence, the study also examined Topio Decoupling Index (2005). The negative energy intensity and carbon intensity effect have shown an improvement in terms of energy use.
ISME
Keywords: Decomposition Analysis; LMDI; CO₂ emission; Economic growth; India; Brazil